Membangun Kompetensi Guru Melalui Supervisi Akademik Kolaboratif di MTs Negeri 10 Jakarta Barat - Dzakwan Dzakwan; Akhmad Shunhaji; Farizal Farizal (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This thesis concludes about the Implementation of Academic Supervision with a Collaborative Approach in Improving the Competence of Mtsn 10 West Jakarta Teachers. This study uses a qualitative approach, with data collection through interview, observation, and document study techniques. The results of these findings reveal the following: First, this study aims to analyze the application of academic supervision with a collaborative approach in MTsN 10 West Jakarta and its impact on improving teacher competence and learning quality. Although academic supervision has been implemented with the aim of improving teacher competence, the implementation of a collaborative approach involving active cooperation between teachers, supervisors, and other related parties has not been fully implemented. This approach, which prioritizes open discussion, sharing experiences, and formulating solutions together, has not been implemented optimally. One of the main challenges in the implementation of collaboration is the limited time and readiness of some teachers to work together openly. These two studies show that the implementation of collaborative-based academic supervision has great potential to create a supportive atmosphere for teachers to share ideas, experiences, and solutions to challenges in teaching. However, the main obstacles that hinder this process include time constraints, differences in teachers' competencies and teaching styles, and the lack of readiness of some teachers to receive feedback or share their teaching methods. Therefore, support measures are needed, such as more flexible scheduling and the use of online platforms that facilitate collaboration without disrupting teaching hours. With the implementation of these steps, it is hoped that a collaborative approach can be implemented more effectively and can improve the quality of education at MTsN 10 West Jakarta optimally.